2007
DOI: 10.1197/j.aem.2007.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Do Knowledge and Experience Have Specific Roles in Triage Decision‐making?

Abstract: Accuracy of triage decisions is a major influence on patient outcomes. Triage nurses' knowledge and experience have been cited as influential factors in triage decision-making. The aim of this article is to examine the independent roles of factual knowledge and experience in triage decisions. All of the articles cited in this review were research papers that examined the relationship between triage decisions and knowledge and/or experience of triage nurses. Numerous studies have shown that factual knowledge is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 28 publications
3
63
2
2
Order By: Relevance
“…Dong et al argue that triage is influenced by training, and that memory and experience lead to subjectivity and inconsistency in the triage process (23,24). They specify that experience is poorly related to the accuracy of triage decisions and that regular updates on the use of CTAS tend to improve the interrater reliability of triage scores (25). The fact that its application varies among experienced users implies that the scale might not be sufficiently restrictive, and that nurses might overly interpret its use and application.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dong et al argue that triage is influenced by training, and that memory and experience lead to subjectivity and inconsistency in the triage process (23,24). They specify that experience is poorly related to the accuracy of triage decisions and that regular updates on the use of CTAS tend to improve the interrater reliability of triage scores (25). The fact that its application varies among experienced users implies that the scale might not be sufficiently restrictive, and that nurses might overly interpret its use and application.…”
Section: Discussionmentioning
confidence: 97%
“…They argue that if the results obtained are satisfactory, then further research is not warranted (16). In addition, Considine et al found no evidence that written case scenarios are less appropriate then other methods to analyze the reproducibility of triage (25). Another study conducted by Considine and colleagues suggested that visual clues added to written scenarios make them more realistic (31).…”
Section: Limitationsmentioning
confidence: 92%
“…Several interview participants observed that as they had been given no formal training in triage decision making, they were entirely reliant on their experience to guide them in practice. Considine et al (2007) note that a significant relationship between experience and accurate triage decision making has not been established and that factual knowledge is more important to accuracy than years of experience. More than 70% of MH triage nurses had experience in community MH; however, very few had experience in child and adolescent psychiatry (14%) or drug and alcohol assessment (20%), and this is despite the fact that MH triage clinicians are expected to be skilled in assessing patients across the lifespan.…”
Section: How Do Mh Triage Clinicians Make Decisions?mentioning
confidence: 96%
“…Seventy-two clinicians from the sample held tertiary qualifications (51.7%), but There were very few clinicians who had experience in child and adolescent, aged MH settings, or drug and alcohol services; however, approximately 60% of the total population had experience in community MH, including CAT teams, Homeless Outreach teams. The triage clinician's level of education and breadth of clinical experience are factors that impact on decision making, and as such, it is important to consider these variables when appraising the decision-making practices of this population (Considine, Botti, & Thomas, 2007).…”
Section: Characteristics Of the Populationmentioning
confidence: 99%
“…4,5 As the entry point for patients coming into hospital systems via the ED, the triage role is central to the efficient delivery of emergency care 6,7 and paramount to patient safety. 2,6,8,9 However, this role is often undertaken in crisis-driven 3 and chaotic 10 settings. Decisions are made in the context of significant time constraints, crowded waiting rooms, and high patient anxiety.…”
mentioning
confidence: 99%